Propolis Immunomodulatory Action - Sforcin, Jose Mauricio; Singh, V. K.; Govil, J. N. (Studium Press Llc, 2010)
Propolis exerts several biological properties, and its immunomodulatory and antitumoral actions have been intensively investigated. In vitro and in vivo experiments demonstrated the modulatory action of propolis on murine peritoneal macrophages, increasing their microbicidal activity. Propolis stimulates the lytic activity of natural killer cells against tumor cells, and increases antibody production. Propolis inhibitory effects on lymphoproliferation may be associated to its anti-inflammatory property. The best results in the immune system were observed when propolis was administered over a short-term to animals. Since humans have used propolis for different purposes, the scientific basis of its properties is important not only for researchers but also for those who use propolis as well.
Keywords: Propolis; Immune system; Immunomodulatory action